DISCOVERING THE SCIENTIFIC AND SPIRITUAL HERITAGE OF IMAM ISA AT-TERMIZI - Kadirova Mamlakt Mominovna (Galaxy International Interdisciplinary Research Journal, 2024)
Imam Isa at-Tirmidhi (Imam Abu Isa Muhammad ibn Isa ibn Sawr at-Tirmidhi) occupies a respected place in Islamic science, known for his contributions to the hadith literature and deep spiritual insights. In this scientific article, the scientific and spiritual legacy of Imam Isa at-Tirmidhi is deeply studied, his scientific achievements, spiritual teachings and lasting legacy in Islamic traditions are highlighted.